Pelatihan Pembuatan Evaluasi Pembelajaran Bagi Guru Berbantu Plugin Autoproctor pada Google Form di Kota Binjai Provinsi Sumatera Utara - Suharyani, Susi; Azhar, Zul; Rambe, Fahrizal (HIMPUNAN DOSEN GEMILANG INDONESIA, 2023)
Technology-based learning is a challenge for teachers in the 21st century. Teachers are required to be proficient in technology in preparing students. Advances in technology make learning evaluation a demand for better and closing opportunities for cheating during exams. Computer applications can be used as a tool to carry out learning evaluation activities. Provision of teachers in making use of technological progress needs to get training in making learning evaluations. This training activity aims to create an online exam application using the Google form with the AutoProctor. The training participants were 30 teachers with undergraduate education backgrounds consisting of teachers of public and private elementary schools, junior high schools and senior high schools in the city of Binjai, North Sumatra. The training activities were carried out for one day. The stages of the activity consist of preparation, implementation, mentoring and evaluation stages. Based on the results of the implementation and evaluation it was concluded that the participants in the online exam preparation training activities were able to make and feel satisfied with performance of the online exam application that was successfully created